"Phonebloks, or a phone developed by its future users" : user experiences of a forum for a modular phone concept - Deseille, Victor (2016)
In late 2013, a project caught my attention as being interesting to me and potentially a lot of others, innovative, and environmentally friendly: a smartphone project called Phonebloks. This timing fitting perfectly with the start of my Master's thesis as well as my personal interests, I observed it to see how it would develop. The official website which was created let users debate in order to decide where this Phonebloks project should go, so I decided to focus my efforts on it. This thesis describes perceptions of users regarding an online forum about a new kind of phone, called Phonebloks. On this forum they can debate about the future of the phone. I based my analysis on research on forums as well as user perception and involvement. I used 869 comments from the forum, and content analysis, with a code book, quantitatively and slightly qualitatively. It was found that communication is widely polite, with very little negative behavior throughout the forum. It was also discovered that visual stimulation, with images instead of text, enables more debate since it draws more attention to the topics. This thesis gave a glimpse as to what a part of users express online what they want to see in the upcoming phones developed in a modular way, and also how they express these wishes.